Eslicarbazepine acetate in post-stroke epilepsy: Clinical practice evidence from Euro-Esli - Sales, Francisco (2020)
Objectives: To assess the effectiveness and safety/tolerability of eslicarbazepine acetate (ESL) in patients included in the Euro-Esli study who had focal seizures associated with post-stroke epilepsy (PSE). Materials and methods: Euro-Esli was a pooled analysis of 14 European clinical practice studies. Effectiveness assessments (evaluated after 3, 6 and 12 months of ESL treatment and at final follow-up ["last visit"]) included rates of response (≥50% seizure frequency reduction), seizure freedom (no seizures since at least the prior visit) and retention. Safety/tolerability was assessed throughout ESL treatment by evaluating adverse events (AEs) and discontinuation due to AEs. A post hoc analysis was conducted of patients with PSE versus patients without PSE ("non-PSE"). Results: Of 1656 patients included in the analysis, 76 (4.6%) had PSE and 1580 (95.4%) had non-PSE. Compared with non-PSE patients, PSE patients were significantly older, had significantly shorter epilepsy duration, significantly lower total baseline seizure frequency, and were treated with significantly fewer prior and concomitant antiepileptic drugs (P < .001 for all). At the last visit, the responder rate was significantly higher in PSE versus non-PSE patients (72.9% vs 60.6%; P = .040), as was the seizure freedom rate (48.6% vs 31.7%; P = .003). After 12 months, retention was significantly higher in PSE versus non-PSE patients (87.8% vs 77.4%; P = .035). The incidence of AEs was similar for PSE versus non-PSE patients (36.0% vs 35.8%; P = .966). Conclusions: These findings suggest that ESL may be an effective and well-tolerated treatment option for patients with focal seizures due to PSE.